2013
DOI: 10.1038/nchembio.1250
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric inhibition through suppression of transient conformational states

Abstract: The ability to inhibit binding or enzymatic activity is key to preventing aberrant behaviors of proteins. Allosteric inhibition is desirable as it offers several advantages over competitive inhibition, but the mechanisms of action remain poorly understood in most cases. Here we show that allosteric inhibition can be effected by destabilizing a low-populated conformational state that serves as an on-pathway intermediate for ligand binding, without altering the protein's ground-state structure. As standard struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 44 publications
2
102
0
Order By: Relevance
“…Traditionally, ligand release has been explained using a simple diffusion model 3 . With advances in experimental methods to investigate the protein dynamics, such as nuclear magnetic resonance, computational simulations and single-molecule techniques, evidence for the role of protein dynamics in ligand dissociation has been provided 9,10,19,20 . Recently, Carroll et al 3 analysed the dynamics at the binding site of DHFR for a series of inhibitors with different binding affinities through nuclear magnetic resonance relaxation dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, ligand release has been explained using a simple diffusion model 3 . With advances in experimental methods to investigate the protein dynamics, such as nuclear magnetic resonance, computational simulations and single-molecule techniques, evidence for the role of protein dynamics in ligand dissociation has been provided 9,10,19,20 . Recently, Carroll et al 3 analysed the dynamics at the binding site of DHFR for a series of inhibitors with different binding affinities through nuclear magnetic resonance relaxation dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…There has recently been growing interest in the regulation of protein functions in an allosteric manner 19,25,[28][29][30][31][32] . However, the operational mechanism of the allosteric regulation remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, relaxation dispersion experiments of CAP-T127L/S128I-cGMP2 complex showed profiles that are characteristic of the absence of any alternative conformational states that form on the ms-μs time scale (the detection limit of the relaxation dispersion experiments is ∼0.5 %). The data suggested that cGMP binding suppresses the active conformation and then results in allosteric inhibition of DNA binding (Tzeng and Kalodimos 2013) (Fig. 2c, d).…”
Section: Allosteric Regulation By Slow Dynamicsmentioning
confidence: 90%
“…cGMP binding to CAP* results in the suppression of the active conformation through an allosteric mechanism. Figure reproduced from Tzeng and Kalodimos 2013 (ΔH) and entropic (ΔS) components. Interestingly, the various CAP proteins bound to DNA using alternative thermodynamic strategies, with some interacting with favorable enthalpy (ΔH) and others with favorable entropy (ΔS) (Fig.…”
Section: Allosteric Regulation By Fast Dynamicsmentioning
confidence: 99%
“…The advantage of R ex experiments is providing not only kinetic, but also thermodynamic, and structural information on transient states, which in turn can serve as new targets for allosteric inhibition and open new possibilities in drug design (Piana et al, 2002;Tzeng and Kalodimos, 2013). Another extensively investigated time regime in proteins is the ps-ns time scale (Farrow et al, 1994).…”
Section: D Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%